2016
DOI: 10.1007/s00268-016-3736-2
|View full text |Cite
|
Sign up to set email alerts
|

Robotic‐Assisted Versus Laparoscopic Left Lateral Sectionectomy: Analysis of Surgical Outcomes and Costs by a Propensity Score Matched Cohort Study

Abstract: Even if feasible and safe, the robotic approach does not seem so far to offer additional benefit in terms of intra- and postoperative outcomes over the laparoscopic approach in patients requiring LLS. Total costs associated with the R-LLS group are not greater than that associated with the L-LLS group, which is the standard of care so far.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 60 publications
0
43
0
Order By: Relevance
“…In case of overlapping populations, the most recent or most informative studies were included in the systematic review (Supplemental Table S2). From the 803 records retrieved, 31 studies were finally deemed eligible, incorporating a total of 1148 patients. The majority of studies were from Europe (14/31), followed by Asia (10/31) and the USA (7/31).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In case of overlapping populations, the most recent or most informative studies were included in the systematic review (Supplemental Table S2). From the 803 records retrieved, 31 studies were finally deemed eligible, incorporating a total of 1148 patients. The majority of studies were from Europe (14/31), followed by Asia (10/31) and the USA (7/31).…”
Section: Resultsmentioning
confidence: 99%
“…A detailed classification of complications according to the Clavien‐Dindo system was provided only in 18 studies (Supplemental Table S4). Overall, grade I/II complications were observed in 12.2%, grade III/IV in 5.9% and grade V in 0.1%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…41 The Henri Mondor Hospital group of Paris, which has an internationally renowned expertise in laparoscopic liver surgery, has published a further, very recent analysis. 42 The authors reported on a propensity-score-matched comparison between laparoscopic and robotic left lateral sectionectomy. Overall, the two techniques were equal on both perioperative and postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Most data were obtained from prospectively maintained databases. Tables 3 and 4 showed the results of nonrandomized comparative studies comparing robotic and laparoscopic partial hepatectomy in patients with minor hepatectomies [18][19][20][21][22][23][24][25] and in patients with minor and major hepatectomies [26][27][28][29] . Although the perioperative outcomes seemed to be similar in both groups, the benefit of robotic approach has been shown in several studies.…”
Section: Robotic Vs Conventional Laparoscopic Partial Hepatectomymentioning
confidence: 99%